Protein deterioration and longevity of quinoa seeds during long-term storage - Castellion, Martina Laura (2010)
Seed protein stability and seed deterioration during storage were studied in seeds of two different quinoa (Chenopodium quinoa Willd.) cultivars, i.e., cv. Ollagüe and cv. Baer II. Germination and viability tests proved that cv. Baer II was more longevous than cv. Ollagüe. Protein insolubilisation was detected during storage and correlated with longevity. However, protein solubility was restored by priming in both cultivars, disregarding their germination capability. Extremely high contents of advanced glycation end-products (AGEs), assessed by carboxymethyllysine (CML) quantification, were obtained from stored seeds as viability was reduced; primed seeds showed slightly lower AGE content, indicating a strong association between quinoa seed ageing and Maillard products accumulation. High intensity fluorescence values were observed in seeds stored in the gene bank bearing 100% germination values, which indicate that the detection of fluorescence is not by itself an appropriate indicator of protein damage by Maillard-type product accumulation in quinoa seeds. This work establishes for the first time a direct association between seed viability and AGE accumulation, due to Maillard reaction, in quinoa seeds.